مصادر الصورة الفنية وأدوات بنائها في شعر رائد المدرسة الأوسية أوس بن حجر: دراسة وصفية وتحليلية. - Al Wahaibi Said Obaid Abdullah Hamed
The study aims at identifying the sources of the artistic image in the poems of the Oussians school of poets. Diwan Aws b Hajar discussed a model for the study. The study focuses on the sources of artistic image in ancient Arabic poetry when the Oussians were specialised, and to identify the most important tools that the Oussians have addressed and discussed the logic of the image art through the use of creative imagination on individual and collective memory consciously or unconsciously. And providing an integrated interpretation of the aesthetics of visual poems and return it to its origins. The researcher also examined the elements of the sources of the artistic image in the geological poetry by determining the structure of the verse in the Oussians to the source of the artistic image through the most important tools: similarity, proximity, shape, interaction, and homogeneity. These procedural tools are revealing to the text, specific to its features. The study aims at reaching the goal for which we have penetrated the text of poetry, highlighting the aesthetic and artistic fascination created by the artistic picture in the text. The study seeks to understand the most important features of the artistic image of the poets of the Oussian school. The methodology used to study the sources of artistic image in the poetry of the Oussian school, the extraction of artistic images. The focus is on the other end, and it defines the source of the image, ie, the substantive-life, and the physical - from which the poets of the Ossian school drew their pictures. The study agreed to adhere to the descriptive analytical approach in general, and did not take advantage of some of the curriculum integration as needed. The study found that the poetry image is the most effective key in revealing the secret of creativity in poet's poetry and the immortality of his art. It opens the way to reveal the hidden life of the poet, to reflect visual and audio images. The image is based on the picture; to approximate the viewer to the recipient; to be influenced by the poet's text. Furthermore, the picture is a painting that accepts everything in the same poet from the repercussions in order to convey to us in a natural color .